2014
DOI: 10.1080/07060661.2014.925001
|View full text |Cite
|
Sign up to set email alerts
|

Control ofSclerotinia sclerotioruminfection in oilseed rape with strobilurin fungicide SYP-7017

Abstract: SYP-7017, a broad-spectrum fungicide, belongs to the chemical group of strobilurins. Baseline sensitivity of Sclerotinia sclerotiorum (Lib) de Bary to SYP-7017 was determined using 120 strains collected during 2010 and 2011 from rapeseed fields without a previous history of strobilurin usage in Jiangsu Province, China. The median effective concentration (EC 50 ) values for SYP-7017 that inhibited mycelial growth ranged from 0.006 to 0.047 µg mL −1 (mean of 0.016 µg mL −1 ). No cross-resistance between SYP-7017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…QoI fungicides have shown perfect control efficacy in many crops and exhibit a broad antifungal spectrum due to their excellent fungicidal effect. [32][33][34][35] However, as a group of fungicides with a single action site, it is much easier to develop QoI-resistant mutants in the laboratory and field. Picoxystrobin, a QoI fungicide, C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QoI fungicides have shown perfect control efficacy in many crops and exhibit a broad antifungal spectrum due to their excellent fungicidal effect. [32][33][34][35] However, as a group of fungicides with a single action site, it is much easier to develop QoI-resistant mutants in the laboratory and field. Picoxystrobin, a QoI fungicide, C.…”
Section: Discussionmentioning
confidence: 99%
“…QoI fungicides, the most successful chemicals in the world, inhibit energy synthesis in plant pathogens by blocking the transfer of electrons in the quinone “outside” site of mitochondria complex III in the electron transport chain. QoI fungicides have shown perfect control efficacy in many crops and exhibit a broad antifungal spectrum due to their excellent fungicidal effect 32–35 . However, as a group of fungicides with a single action site, it is much easier to develop QoI‐resistant mutants in the laboratory and field.…”
Section: Discussionmentioning
confidence: 99%
“…The fungicidal potentials of carbendazim, mancozeb and iprodione were reported against S. sclerotiorum in previous studies ( Mueller et al . , 2004 ; Singh et al, 2014 ; Wang et al, 2014 ). Similarly, Wilson et al (2005) reported that Ca in the form of Ca(OH) 2 inhibited S. minor ’s sclerotial germination and infection at the collar region of lettuce plants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, isolates resistant to strobilurin fungicides have been reported in several important fungi, such as Alternaria alternata , Pseudoperonospora cubensis , and Blumeria graminis f.sp. tritici [19,20,21,22]. Owing to advantages in environment and health safety, and to minimize the risk of resistance development, many antifungal agents from plant extracts have been studied, such as limonoids from Khaya ivorensis A Chev [23], 1,2-Dihydro-6α-acetoxyazadirone from the fruit of Chisochton paniculatus (Roxb.)…”
Section: Introductionmentioning
confidence: 99%